Influence of internal curing on compressive strength and drying shrinkage of super-sulfated cement mortar - Tran, Vu An; Nguyen, Hoang Anh; Bui, Le Anh Tuan (CTU Journal of Innovation and Sustainable Development, 2023)
The current study aims at assessing the effect of using cold-bonded fly ash based artificial lightweight aggregate (ALWA) as an internal curing (IC) agent on the compressive strength and drying shrinkage of a typical super-sulfated cement (SSC) produced with a mixture of 85% slag, 10% gypsum, and minor amount of 5% blended Portland cement (PCB). The ALWA was used as partial replacement of fine aggregate (FA) at values of 25, 50, 75, and 100 vol.%. Experimental results showed that the ALWA partially replacing FA in range of 25–100 vol.% significantly decreased both the unit weight and dried density of the fresh and hardened IC-SSC mortars at average values of 13.9% and 20.0%, when compared with the reference SSC mortar, respectively. The ALWA increment continuously reduced the compressive strengths of the hardened IC-SSC mortars. But, at 28 days of curing, the hardened IC-SSC mortar containing the ALWA amount partially replacing FA up to 50 vol.% showed compressive strength reaching 89.3%, and comparable or slightly lower drying shrinkage in comparison with the reference SSC mortar without the IC agent.